2018
DOI: 10.4269/ajtmh.17-0998
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies in Melioidosis: The Role of the Indirect Hemagglutination Assay in Evaluating Patients and Exposed Populations

Abstract: Abstract.Melioidosis is a major neglected tropical disease with high mortality, caused by the Gram-negative bacterium Burkholderia pseudomallei (Bp). Microbiological culture remains the gold standard for diagnosis, but a simpler and more readily available test such as an antibody assay is highly desirable. In this study, we conducted a serological survey of blood donors (n = 1,060) and adult melioidosis patients (n = 200) in northeast Thailand to measure the antibody response to Bp using the indirect hemagglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 63 publications
4
35
1
5
Order By: Relevance
“…On the other hand, the HH cohort and control cohorts in general had relatively low humoral immune responses to all 3 Burkholderia antigens but profound cellular immune responses. We showed that just over half of the acute melioidosis patients were positive by IHA; previous work in our group has shown that a significant proportion (12.6%) of melioidosis patients never seroconvert (16). We do not have enough information to confirm whether the persistence of seropositivity against B. pseudomallei in healthy persons is associated with latent infection or with successful clearance of B. pseudomallei after exposure events.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…On the other hand, the HH cohort and control cohorts in general had relatively low humoral immune responses to all 3 Burkholderia antigens but profound cellular immune responses. We showed that just over half of the acute melioidosis patients were positive by IHA; previous work in our group has shown that a significant proportion (12.6%) of melioidosis patients never seroconvert (16). We do not have enough information to confirm whether the persistence of seropositivity against B. pseudomallei in healthy persons is associated with latent infection or with successful clearance of B. pseudomallei after exposure events.…”
Section: Discussioncontrasting
confidence: 76%
“…Our team and others have shown that surviving melioidosis patients have elevated CD4 and CD8 T-cell-mediated interferon γ (IFN-γ) responses to B. pseudomallei compared with deceased case-patients (13,14). Along with key protective immunity conferred by cellular immune responses, humoral immunity against BP infection has been demonstrated to be a component of protection in rodent models (15), although antibody levels measured by indirect hemagluttination assay were not significantly associated with survival (p>0.05) in human patients after adjusting for other parameters (16). Our study aimed to characterize the relationship between the human B. pseudomallei-specific immune response and responses to B. thailandensis and BTCV.…”
mentioning
confidence: 99%
“…DN T cells have been previously identified as important mediators for the control of intracellular bacterial infection in mouse models of Francisella tularensis and M. tuberculosis infection , which warrants further investigation in the context of melioidosis and DM comorbidity. In addition to these cellular changes, we measured significantly higher bacterial antibody titers in DM survivors of acute melioidosis as previously reported in Australia and Thailand , and this correlated to the number of circulating NK cells. In some endemic regions, up to 80% of children produce antibodies to BP by the age of 4 years .…”
Section: Discussionsupporting
confidence: 73%
“…Current serological methods on the other hand often suffer from a lack of standardization, a low sensitivity and high background seropositivity. This includes the indirect hemagglutination assay (IHA), which is the serological standard test for melioidosis in many endemic regions, whose sensitivity might be as low as 56%, and is commonly positive in the endemic population [ 27 29 ]. There is known cross-reactivity of antibody and cellular responses to B .…”
Section: Introductionmentioning
confidence: 99%